Analysis of Village Financial Management in Ara Condong Village, Stabat District, Langkat Regency - Lubis, Mutiara Aulia; Siregar, Oktarini Khamilah; Nasution, Dito Aditia Darma (PT FORMOSA CENDEKIA GLOBAL, 2024)
Examining how well Ara Condong Village's financial management adheres to the Minister of Home Affairs' Regulation No. 20 of 2018 is the primary goal of this research. The village is located in Stabat District, Langkat Regency. Qualitative descriptive research based on interviews, observations, and documentation is employed. The study's findings provide light on how accountability has been integrated into all aspects of village financial management, from planning to implementation, recording to reporting. Not all indicators are up to par, though; one area that needs improvement is the way the community is informed about the progress being made with the Village Budget. In order to make the management of village fund finances more open and responsible, this study stresses the significance of training and involvement for village officials.